The Grammar of Gender Ideology: The Press Coverage of Sexual Violence in Turkey and the Passive Voice - Sevda Numanbayraktaroğlu (European Journal of Turkish Studies)
This research critically examines the Turkish press coverage of sexual violence during the growing hegemony of neoliberal governmentality in Turkey. Through a critical discourse analysis of the newspaper Hürriyet’s reports on rape cases during the last 20 years, I aim to decipher the structures of power and gender regimes reflected in these reports. To this end, I critically examine the levels of agency and responsibility that reporters attribute to perpetrators and survivors of rape through the use of passive and active voice. The analysis reveals that the media reports of rape characterized male rapists as aggressive criminal agents who were helpless against the police and the legal system. Female survivors, on the other hand, were cast as autonomous agents who became helpless victims of rape (sometimes due to their naiveté) and reclaimed their agency with the help of the police and the legal system. The results point to a transformation of the traditional conceptions of rape and the mainstream gender ideologies as the outcome of two oppositional forces: neoliberal familism and feminist ideology.